ANALISIS PROFIL PEDAGOGICAL KNOWLEDGE, CONTENT KNOWLEDGE, DAN PEDAGOGICAL CONTENT KNOWLEDGE GURU PENDIDIKAN ANAK USIA DINI DI RA MUSLIMAT NU 09 INDONESIA, TASKI AL-MA’ARIF MALAYSIA, DAN ANUBAAN SINGHANAKHON WITTAYA NUSORN SCHOOL THAILAND: ANALYSIS OF PEDAGOGICAL KNOWLEDGE, CONTENT KNOWLEDGE, AND PEDAGOGICAL CONTENT KNOWLEDGE PROFILES OF EARLY CHILDHOOD EDUCATION TEACHERS AT RA MUSLIMAT NU 09 INDONESIA, TASKI AL-MA’ARIF MALAYSIA, AND ANUBAAN SINGHANAKHON WITTAYA NUSORN SCHOOL THAILAND - Rizqiyyah, Reza Zaidatur; Dewi, Mutiara Sari; Sulyandari, Ari Kusuma; Kawklang, Siraprapa (Thufuli, 2024)
Early childhood education is crucial for child development, requiring well-prepared teaching staff, a conducive learning environment, and a robust curriculum. Teachers, as the primary figures interacting with students, play a vital role. Differences in curriculum, culture, and educational elements in Indonesia, Malaysia, and Thailand result in varying profiles of PAUD teachers' pedagogical content knowledge. This research uses quantitative methods to explore these differences among early childhood education teachers at RA Muslimat NU 09 (Indonesia), Taski Ma'arif (Malaysia), and Anubaan Singhanakhon Wittaya Nusorn School (Thailand). The study identifies factors that support and hinder the profiles of pedagogical content knowledge in these institutions. The research results will highlight the percentages of pedagogical knowledge, content knowledge, and pedagogical content knowledge among PAUD teachers in these schools, emphasizing the differences. Findings show that RA Muslimat NU 09 teachers have 79.6% in these areas, Taski Ma'arif teachers have 74.1%, and Singhanakhon Wittaya Nusorn School teachers have 78%. That’s means teachers' pedagogical content knowledge competencies in Indonesia, Malaysia, and Thailand do not show significant differences. The main difference is that teachers in Indonesia have relevant educational backgrounds, whereas in Malaysia and Thailand there are still teachers with educational backgrounds that are not relevant.